ADAPTIVE COMMUNICATION STRATEGIES FOR INDUSTRIAL WIRELESS SENSOR NETWORKS: PRIORITY-BASED CHANNEL SCHEDULING AND ROUTE DISCOVERY - Dr V Gnanasekar, Dr R Kannan (Chelonian Research Foundation, 2023)
This study explores how Priority-based channel management and Route Finding might be combined to improve communications in Commercial wireless sensor networks (IWSNs). Industrial settings provide particular difficulties that necessitate adaptive techniques for reliable and effective data transfer. Priority-based Channel Scheduling distributes resources according to the importance of the data, avoiding congestion and guaranteeing the prompt delivery of crucial information. In addition, Route Discovery adapts to changing network topologies by dynamically identifying the best routes. The paper evaluates the suitability of popular protocols for communication such as WirelessHART, ISA100.11a, as well as LoRaWAN for various industrial environments through a thorough comparative analysis. Based on factors including data rate, assortment, usage of power, and flexibility, each protocol is carefully examined. The study focuses on the applications of integrated communication techniques across the infrastructure, administration, energy, and industrial industries. The operational effectiveness, safety protocols, and compliance with laws are considerably improved by priority-based stream scheduling as well as route discovery. Recommendations cover stringent security measures, industry-specific modification, and empirical evaluation in real-world circumstances. Future research examines the integration of machine learning, adaptive protocol adaption, and cross-industry adaptability. Standardization and industrial adoption are other goals of the study. Keywords- message attenuation, changing network, transmissions, shifting network, Identification mechanisms